Peran Petugas Kesehatan dan Pengawas Minum Obat dengan Kepatuhan Minum Obat pada Pasien Tuberkulosis - Mariska, Refita Dwi; Lestari, Trijati; Pramestirini, Rizky Asta (Jurnal Keperawatan Florence Nightingale, 2025)
One of the main barriers to effective tuberculosis treatment is patients’ low level of medication adherence. This issue often results in incomplete treatment and thus requires support from healthcare workers and treatment supervisors (PMOs). This study aimed to examine the relationship between the roles of healthcare workers and PMOs with medication adherence among tuberculosis patients at Lamongan Community Health Center. A cross-sectional design was employed, utilizing total sampling of 52 tuberculosis patients. Data were collected using structured questionnaires on the roles of healthcare workers, questionnaires PMOs, and as well as the MMAS-8 questionnaire to assess adherence. The majority of tuberculosis patients are 45–59 years old, male, high school graduate, and unemployed. Pearson correlation analysis revealed significant positive relationships between healthcare workers’ roles (p = 0.000; r = 0.689), and PMOs (p = 0.000; r = 0.664) with medication adherence. The results indicate that healthcare workers, and PMOs play a vital role in supporting TB patients’ recovery and serve as a foundation for strategies aimed at improving adherence. Their ability to provide continuous education, supervision, motivation, and emotional support helps enhance adherence, reduce relapse and drug resistance risks, and prevent further disease transmission. Tuberculosis patients are expected to be disciplined in taking medication and communicating with health workers or PMO if they experience obstacles so that treatment is successful.